The Competitiveness Of Indonesian Frozen Shrimp (HS030617) Export in European Market - Jesica Karindra Agustia; Ignatia Martha Hendrati (UNIVED Press, 2024)
Shrimp is one of the top ten major commodities that significantly contribute to foreign exchange earnings in the fisheries sub-sector. Indonesia is among the world's fourth-largest exporters of frozen shrimp commodities. The European market holds a 25% share as one of the main global importers of shrimp products. The research method employed includes Revealed Comparative Advantage (RCA) to analyze competitiveness through comparative advantage and Export Product Dynamic (EPD) to assess competitive positions in the European market from 2018 to 2022. The research results indicate that Indonesian frozen shrimp (HS 030617) exhibits high competitiveness in the European market, except in Italy and Spain. Meanwhile, through competitive advantage, the competitive export position of Indonesian frozen shrimp commodities (HS 030617) varies in the European market.